2023
DOI: 10.3389/fanim.2023.1233273
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of yeast-based additives, as an alternative to ionophores, on rumen fermentation of ruminant diets using an in vitro gas production system

Amanda Regina Cagliari,
Elaine Magnani,
Fernanda Rigon
et al.

Abstract: IntroductionThe study aimed to assess yeast-based additives' effects, as monensin alternatives, on rumen fermentation parameters, greenhouse gas emissions, and ruminal kinetics of ruminant diets using an in vitro system. Three experiments were conducted, each individually evaluating escalating levels of three yeast-based additives.MethodsThree experiments were designed: Experiment 1 evaluated prebiotic blend 1—yeast culture [Saccharomyces cerevisiae (Scer)], beta-glucans, fructooligosaccharides, galactooligosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
(53 reference statements)
1
0
0
Order By: Relevance
“…Generally, higher gas production means higher degree of substrate fermentation (Zhang et al 2020 ). A recent study found that yeast products supplementation significantly increased the maximum gas production of fermentation substrate as well as GP 48 (Cagliari et al 2023 ), which were in accordance with our results. The lower gas production in CON group was mainly due to the insufficient activity of microorganisms.…”
Section: Discussionsupporting
confidence: 93%
“…Generally, higher gas production means higher degree of substrate fermentation (Zhang et al 2020 ). A recent study found that yeast products supplementation significantly increased the maximum gas production of fermentation substrate as well as GP 48 (Cagliari et al 2023 ), which were in accordance with our results. The lower gas production in CON group was mainly due to the insufficient activity of microorganisms.…”
Section: Discussionsupporting
confidence: 93%